(untitled) (AmeriQuests, 2019)
Race, Criminal Justice, and Migration Control: Enforcing the Boundaries of Belonging, edited by Mary Bosworth, Apla Parmar, and Yolanda Vazquez, is an anthology of essays involving the intersectionality of race separated into four sections: 1) Race, Borders, and Social Control; 2) Race, Policing, and Security; 3) Race, Courts, and the Law; and 4) Race, Detention, and Deportation. As an introduction to intersectionality between race, and gender and class, this anthology gives a somewhat comprehensive compilation of migration issues stemming in countries that exercise firm control over migration of incoming migrants and exiting migrants. Each article focuses on an issue ongoing with a specific population of people, and how the mechanisms in place for migration function criminally and divisively.